Pengaruh Likuiditas terhadap Pertumbuhan Laba Akuntansi dengan Ukuran Perusahaan Sebagai Variabel Moderasi: Studi Kasus pada Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Yohanes August Goenawan; Atika Purnamasari; Intan Agustin (LPPM STIE PPI, 2025)
Introduction/Main Objectives: This study aims to determine the effect of liquidity on accounting profit growth with company size as a moderating variable in the food & beverage sector. Background Problems: There is an observable instability in profit growth caused by suboptimal There is instability in profit growth due to less than optimal liquidity management and differences in company size that affect its financial and operational capabilities in the food and beverage industry. Novelty: Conducting tests on different units of analysis and periods from previous studies. Research Methods: The research method used is a quantitative approach with a sample of 6 companies over five years, and the test tool used is SPSS. Finding/Results: Liquidity affects profit growth, while the significance value between liquidity and company size has a significant effect together on profit growth in the food & beverage sector listed on the Indonesia Stock Exchange for the 2019-2023 period. Conclusion: This finding indicates that companies need to expand and improve operational efficiency so that company size can increase, thereby gaining benefits from economies of scale.